Geology of the Indus Suture Zone in the Mingora-Shangla Area of swat, N. Pakistan - Kazmi, A.H.; Lawrence, R.D.; Dawood, H.; Snee, L.W.; Hussain, S.S. (Journal of Himalayan Earth Sciences, 1984)
In the Mingora area the Indus suture zone is largely composed of metamorphosed ophiolites and melanges which have been wedged in between the Indo-Pakistan crustal plate and the Kohistan andesitic arc block. The Indo-Pakistan subcontinental sequence is made up of the twice metamorphosed Munglaur crystalline schists, the intrusive Swat granite gneiss, and the unconformably overlying once metamorphosed Alpurai and Saidu schists. The recognition of this unconformity requires major revision of the stratigraphic correlation of these units which were previously all considered to be Precambrian. Those above the unconformity are probably Phanerozoic, and the Saidu schist may be the local a metamorphosed equivalent of the Indus flysch of Ladakh. The ophiolitic and related rocks of the Indus suture melange group are subdivided into three separate units. The Shangla blueschist melange is locally present in the north and represents n subduction complex developed adjacent to the Kohistan arc, The Charbagh greenschist melamge crops out in the centre of the group and could be of either mid-oceanic island or island arc origin. The Mingora ophiolitic melange is abduction complex. It is characterized by metamorphism to talc-dolomite schist and emerald mineralization.